Kindergarten class. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a class of kindergarten evacuees in costume preparing to take part in a baby parade and show held at Santa Anita, California Assembly Center.